Study of coordination environments around Pd and Pt in a Pd-core Pt-shell nanoparticle during heating. (May 2016) - Nishimura, Y F; Hamaguchi, T; Yamaguchi, S; Takagi, H; Dohmae, K; Nonaka, T; Nagai, Y
Abstract: Local coordination environments around Pd and Pt in a Pd-core Pt-shell nanoparticle (NP) at temperatures ranging from 473 to 873 K was evaluated by utilizing in situ XAFS measurement technique to investigate the temperature range in which a core-shell structure is preserved. The core-shell structure was considered to be kept up to 673 K and start to change at about 773 K. Heating to 873 K accelerated atomic mixing in the core-shell NPs. Catalytic properties of the present Pd-core Pt-shell NP are available in the stoichiometric C3 H6 -O2 atmosphere at temperatures less than 773 K at most.